Behind The Filter: Self-Acceptance And Social Comparison Among Instagram Users In Early Adulthood - Khaifa Diva Maharani; Hazhira Qudsyi (Green Publisher, 2025)
This research is proposed to determine the relationship between self-acceptance and social comparison. The hypothesis of this study is that there is a negative relationship between self- acceptance and social comparison in early adult Instagram social media users. The data collection technique used was purposive sampling technique. Research respondents are 18-25 years old and actively using social media Instagram. Respondents totaled 346 people. The measuring instrument used is an adaptation of The-Iowa Netherlands Comparison Orientation Measure (INCOM) scale on social comparison variables and an adaptation of the Self- Acceptance scale on self-acceptance variables. The results showed that there is a significant negative relationship between self-acceptance and social comparison with r = -0.150 and p = 0.003 (p < 0.05). This means that the higher of self-acceptance, the lower social comparison. Conversely, the lower of self acceptance, the higher social comparison. Based on these results, the research hypothesis are acceptable.